PENGARUH PEMBERIAN KOMPOS TANDAN KOSONG KELAPA SAWIT PADA TANAH ALUVIAL TERHADAP SERAPAN N, P, DAN K TANAMAN MELON - Catur Rizky Rahman; Asrifin Aspan; Joni Gunawan (Jurnal Sains Pertanian Equator, 2019)
ABSTRACT      Utilization of Alluvial soil as a growth medium, often faced with various limiting factors such as varying levels of fertility, diverse soil acidity, low organic matter content and availability of nutrients, especially nitrogen, phosphorus, and potassium.The is research was conducted in the Faculty of agriculture experiments station, Tanjungpura University. The Method used in the study was field experiment with complete design of stacaments of oil palm empty fruit bunces compost application. The compost application consists of p1 = 0 g/polybags, p2 = 105 g/polybags, p3 = 155 g/polybags, p4 = 205 g/ polybags, p5 = 255 g/polybags. Each treatment is repeated 4 times and each unit ansist of one melon plant per polybag thus thare was 20 plant for field experiment. The results showed that the compost of palm oil blanks is real effect on the soil pH observation variable, but has no noticeable effect on the absorption of nitrogen, phosphorus, and potassium plant and dry weight of plants. Based on the results of the analysis, it can be seen that soil pH before treatment is 4.15 (very sour), after given the average treatment of soil pH increases range from 6.10 (somewhat sour)-6.86 (Neutral). Nitogen-Total soil before treatment is 0.72 % (high), after treatment increased to 0.79 %-0.96 % (very high). -Available soil before treatment is 9.67 ppm (very low), after treatment increased to 33.99 ppm (height)–43.17 ppm (very high). Potassium can be exchanged before the treatment of 0.33 cmol (+) kg-1 (medium), after which the treatment is increased to 0.48 cmol (+) kg-1 (medium)–0.81 Cmol (+) kg-1 (high). Based on the results of the research of the average-the highest rate of compost is the effect of oil palm waste for nitrogen absorption, phosphorus, potassium and dry weight of plants in the treatment of P4 (205 g tkks). This has been optimized for the optimal compost delivery of palm oil to the alluvial soil. Key words: Palm Oil, Composting, Alluvial Soil